A depressurized tank that is used for sand -fixation plant moist irritating a little - ZHAO TONG; LIU WENGUANG; BAI GUILIN; SHI RUN; FAN YANWEI (2017)
A depressurized tank that is used for sand -fixation plant moist irritating a little, have one will decline intercalated duct (3) tile in sand blown by the wind soil furface face, fill the moist sand blown by the wind soil of water after the fluting form soil box (1), be the bottom aspect of constituteing by whole trunk corn stalk (2), little intercalated duct (3) and leaf (4) at the bottom of soil box (1), wheatgrass (6) vertical place in bits of broken glass corn stalk (5) on of making by trussing together is filled in soil box (1) by bits of broken glass corn stalk (5) on bottom aspect upper portion, fill sand blown by the wind soil (7) in the gap of wheatgrass (6), constitute grass grid sand barrier after wheatgrass (6) are fixed. 用于固沙植物微润灌的减压槽，有将微润管（3）平铺于风沙土表面、充水湿润风沙土后开槽形成土槽（1），在土槽（1）的最底层是由整株玉米秸秆（2）、微润管（3）和叶子（4）组成的底层层面，在底层层面上部由碎玉米秸秆（5）填充于土槽（1）内，扎制的麦草（6）竖直放置于碎玉米秸秆（5）上；麦草（6）的缝隙中填注风沙土（7），麦草（6）固定后组成草方格沙障。